(untitled) (Research, Society and Development, 2022)
In Brazil, the Plant Variety Protection Law has broadened the conditions for appropriation by institutions that research new plant genotypes. Since then, the use of protected cultivars implies the payment of royalties to their respective breeders. This paper suggests a theoretical model to help estimate the technological evolution of cultivars and its contribution to the collection of royalties. The model was formulated based on meta-analysis data in which it was verified how the royalty rate for protected cultivars is defined and how these could be weighted in the technological evolution model. Definition of variables according to cultivar and production area. Simulations analyzed for farmer’s profit. It was verified that homoscedasticity was not necessary for the simple purpose of predicting values through the regression model. However, the Breusch-Pagan and Durbin-Watson tests were performed to check for violation of the residuals. The estimation of the Technological Evolution of Cultivars (cotton and sugarcane) showed similarities between the agronomic characteristics according to the Wilcoxon test. Considering the technological evolution of each cultivar the correction equation was proposed to the royalties charged on cotton cultivars.The correction equation was proposed to the royalties charged on sugarcane cultivars. The linear regression model ratified the use of the correction model that may be used in the valuation of royalties and that may help in the identification of the technological evolution of cultivars.